Penerapan Pompa Tanpa Listrik (Heron’s Fountain) untuk Hidroponik DFT (Deep Flow Technique) di Kelurahan Sukamerindu Kecamatan Sungai Serut Kota Bengkulu - Nanang Sugianto; Irkhos Irkhos; Supiyati Supiyati; Helfi Eka Saputra (Universitas Mathla'ul Anwar Banten, 2020)
THE APPLICATION OF NON-ELECTRIC PUMP (HERON’S FOUNTAIN) FOR DFT HYDROPONIC (DEEP FLOW TECHNIQUE) IN SUKAMERINDU, SUNGAI SERUT, BENGKULU CITY. Science and technology-based community engagement about the application of non-electric pump (Heron’s Fountain) for DFT hydroponics (Deep Flow Technique) have been carried out for mother group (respondent) in Sukamerindu, Sungai Serut, Bengkulu City. The aim of this activity is to apply the Appropriate Technology like hydroponics and Heron’s Fountain pumps. The methods of this activities are carried out by training which include socialization and field practice. This program produces 5 hydroponics which are equipped with Heron’s Fountain pumps and brief guidebook about of technologies. The application of the Heron’s Fountain pump for DFT hydroponics was effective in circulating nutrients for hydroponic plants. The Heron’s Fountain pump works temporarily for 45 minutes (10 liters). It was considered sufficient to circulate nutrients for hydroponic plants as evidenced by the same quality for all plants. All plants grow optimally and more yields than initial estimates. The planting period to harvest using hydroponic technology and the Heron’s Fountain pump is quite short, which is approximately 2.5 months. The use of these two technologies helps partners to start farming without using soil media. The cost of making and operating both systems so as to increase the interest of respondent to implement them independently.